A new method based on energy principle to predict uniaxial stress–strain relations of ductile materials by small punch testing. (April 2018) - Peng, Yun-qiang; Cai, Li-xun; Chen, Hui; Bao, Chen
Highlights: A novel model with only three parameters to describe the relation among load, displacement and material properties is proposed based on energy principle, and the solution for obtaining property parameters of materials is explicit and simple. The sizes of the specimens are in millimeter-scale, it is very convenient to obtain the local mechanical properties of small size components or welding materials. For a large amount of imaginary materials, the predictions by our method are proved to agree well with the corresponding FEA results. For some engineering materials at elevated temperature, the predicted stress–strain curves and tensile strengths are proved to be consistent with tensile results. Abstract: Uniaxial stress–strain relations of ductile materials are the most fundamental requirement for the design and safety assessment of structures. In this paper, a novel small punch testing (SPT)-related stress–strain relation (SPT-SR) model is proposed to predict the stress–strain relations of materials on the basis of equivalent energy principle. To examine the validity of the model, numerical simulations by finite element analysis (FEA) with a series of hypothetical materials with different Hollomon's material parameters were carried out. The results demonstrate that the uniaxial stress–strain relations predicted by SPT-SR model from simulated load-displacement curves are in good agreement with the properties of hypothetical materials used in FEA. Furthermore, SPT experiments and tensile tests for four steels (P92, DP600, Q345B, A508-III) at room temperature and 300 °C were conducted. The stress–strain relations predicted by SPT-SR model agree well with the tensile results generated from finite-element-analysis aided testing (FAT) method. Compared with the tensile strengths obtained by uniaxial tensile tests, they can also be well determined based on the strength coefficient and strain hardening exponent predicted by SPT-SR model. Graphical abstract: Image, graphical abstract